2020
DOI: 10.2174/1874434602014010174
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perception of the Clinical Learning Environment

Abstract: Introduction: Clinical learning environment placements provide opportunities for students to develop their skills, socialize to the profession and bridge the gap between academic and workplace learning. This study was conducted to investigate Saudi nursing students’ perceptions of their clinical learning environment and supervision in the hospital setting. Methods: A sample of 90 final year student nurses completing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Furthermore, female nurses with diploma showed lower correlations between stress and coping in all aspects than all sample participants. This result is similar to another study conducted in Saudi Arabia (Alammar et al, 2020) and could be attributed to the smaller sample size for female nurses with diploma degree.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, female nurses with diploma showed lower correlations between stress and coping in all aspects than all sample participants. This result is similar to another study conducted in Saudi Arabia (Alammar et al, 2020) and could be attributed to the smaller sample size for female nurses with diploma degree.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the present study were thus similar to the literature in terms of nursing anxiety and self-confidence with clinical decision-making scores. Nursing students are expected to be able to make rapid and accurate clinical decisions as a result of their theoretical and practical education 39 …”
Section: Discussionmentioning
confidence: 99%
“…Nursing students are expected to be able to make rapid and accurate clinical decisions as a result of their theoretical and practical education. 39…”
Section: Discussion Nursing Anxiety and Self-confidence With Clinical...mentioning
confidence: 99%
“…A gap between abstract, theoretical knowledge and practical skills has been identified in the literature. For instance, in a cross-sectional study that sought to explore the clinical learning environment of nursing students, the students expressed that they were not adequately prepared to handle the medication administration process at the beginning of their clinical rotation (5). Further, literature has shown that nursing students submit the most significant number of medication error reports that reach the patient, accounting for up to 44.8%, ranked second among all medical errors (6,7).…”
Section: Introductionmentioning
confidence: 99%